SISTEM PAKAR MENDIAGNOSA PENYAKIT HEWAN TERNAK LEMBU DENGAN MENGGUNAKAN METODE CERTAINTY FACTOR - Gunawan, Dedy; Sulindawaty, Sulindawaty (Majalah Ilmiah Kaputama, 2019)
In the field of animal husbandry, especially in cattle, the expert system aims to help facilitate the diagnosis of diseases in cattle. The low ability of livestock to meet the need for beef meat and milk is caused by many problems. It could be one of them is a disease. Such as Abscess, Ascariasis, BEF, Bloat, Endometritis, Entritis, Mastitis, Omphaltis, Pneumonia, Retention, Scabies. The emergence of these diseases may be due to the care factors of the breeders so that it affects the health of the bull. the application of the Certainty factor method in the diagnosis of ox disease was built in order to have benefits for the breeders as a consultation media that replaced experts or veterinarians.